LEGAL ANALYSIS OF THE QUALITY OF LAW ENFORCEMENT HUMAN RESOURCES ON THE EFFECTIVENESS OF ERADICATING NARCOTICS CRIME IN BATAM CITY - Erniyanti Erniyanti; Ramlan Ramlan (Faculty of Law, Universitas Pekalongan, 2024)
This paper presents a legal analysis of the quality of human resources of law enforcement and its impact on the effectiveness of eradicating drug crimes in Batam City. Using a normative legal approach, this study examines relevant laws, court decisions, and policies to assess the skills, training, and ethical behavior of law enforcement personnel. The study findings indicate that although Indonesia's legal framework provides a strong foundation, gaps in training, resource allocation, and ethical oversight limit the effectiveness of drug law enforcement in Batam. In addition, challenges such as interagency cooperation deficits, the complexity of drug crime networks, and corruption in law enforcement further undermine efforts to combat drug trafficking. The paper concludes by recommending improvements in law enforcement training, resource investment, interagency collaboration, and anti-corruption measures to improve the effectiveness of drug law enforcement in Batam City.